2021
DOI: 10.3389/fpls.2021.696698
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Characterization and Expression Analysis Provide Basis to the Biological Function of Cotton FBA Genes

Abstract: Fructose-1,6-biphosphate aldolase (FBA) is a multifunctional enzyme in plants, which participates in the process of Calvin-Benson cycle, glycolysis and gluconeogenesis. Despite the importance of FBA genes in regulating plant growth, development and abiotic stress responses, little is known about their roles in cotton. In the present study, we performed a genome-wide identification and characterization of FBAs in Gossypium hirsutum. Totally seventeen GhFBA genes were identified. According to the analysis of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 60 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…This finding aligns with observations in other plant species, three have been identified in Triticum aestivum ( Lv et al, 2017 ), two in B . napus ( Zhao et al, 2019 ), and four in cotton ( Li et al, 2021 ). The amino acid numbers of these genes ranged from 1,352 to 1,383, with exon numbers between 41 and 42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding aligns with observations in other plant species, three have been identified in Triticum aestivum ( Lv et al, 2017 ), two in B . napus ( Zhao et al, 2019 ), and four in cotton ( Li et al, 2021 ). The amino acid numbers of these genes ranged from 1,352 to 1,383, with exon numbers between 41 and 42.…”
Section: Discussionmentioning
confidence: 99%
“…The available genome sequences of potatoes ( Pham et al, 2020 ; Zhou et al, 2020 ; Zhang et al, 2021 ) facilitate their use in potato growth and development. Members of the FBA gene family have been identified in different species, with eight identified in Arabidopsis thaliana ( Lu et al, 2012 ), eight in Solanum lycopersicum ( Cai et al, 2016 ), 22 in Brassica napu s ( Zhao et al, 2019 ), 16 in Nicotiana tabacum ( Zhao et al, 2021 ), and 17 in cotton ( Li et al, 2021 ). When expression of potato chloroplast aldolase (Registry Number: Y10380) was inhibited using antisense repression of expression technology, the photosynthesis of plants was decreased to significantly affect the sugar and starch contents of potatoes ( Haake et al, 1999 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a result of our study, Pvul-FBA genes carrying the FBA domain were determined in beans. Diverse FBA gene members have been found in Spinach oleracea (Pelzer-Reith et al, 1993), Oryza sativa (Kagaya et al, 1995), Zea mays (Dennis et al, 1988), Nicotiana tabacum (Yamada et al, 2000), A. thaliana (Lu et al, 2012), S. portulacastrum (Fan et al, 2009) Solanum lycopersicum (Cai et al, 2016), Triticum aestivum L. (Lv et al, 2017), Brassica napus (Zhao et al, 2019), and Gossypium hirsitum (Li et al, 2021). Whole Genome Folds or polyploidy is a common phenomenon in nature (Wendel, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The decline in the expression of the FBA gene showed that the biomass of the tomato decreased (Cai et al, 2018). Diverse insider of the FBA gene family have been defined and characterized in spinach (Pelzer-Reith et al, 1993), rice (Kagaya et al, 1995), corn (Dennis et al, 1988), tobacco (Yamada et al, 2000), Sesuvium portulacastrum (Fan et al, 2009), Arabidopsis (Lu et al, 2012), tomato (Cai et al, 2016), Triticum aestivum L. (Lv et al, 2017), Brassica napus (Zhao et al, 2019), and cotton (Li et al, 2021). As a result of the research, no study was found related to the genome-wide analysis of the FBA gene members in the common bean plant.…”
Section: Introductionmentioning
confidence: 99%
“…SuSy is a key enzyme in sucrose metabolism and is responsible for catalyzing the reversible reaction between sucrose catabolism and synthesis in plants: sucrose + uridine diphosphate (UDP) 17 of 22 nthetic ability caused by Cd may be related to the expression level of key enzyme the Calvin cycle, while NaHS pretreatment enhanced photosynthetic ability by g the expression level of down-regulated genes [66]. Chloroplast FBA is a critical that controls the photosynthetic rate of plants and plays an essential role in coping iotic stress [67]. In the present study, the up-regulated expression of TaFBA may curred due to the inhibition of photosynthesis in wheat seedlings under Cd stress r to supplement the energy deficiency caused by the inhibition of photosynthesis asing glucose metabolism and maintaining the normal growth and physiological of plants.…”
Section: Nahs Pretreatment Regulates the Related Gene Expression In W...mentioning
confidence: 99%